A systematic review of mother-daughter interventions targeting physical activity. (20th October 2021) - Brennan, C; O' Donoghue, G; Hall, A; Keogh, A; Matthews, J
Abstract: Background: Growing gender disparities in levels of physical inactivity put women and female youths at a greater risk of associated health problems. Mother-daughter interventions have been proposed as means to promote physical activity in this at-risk cohort. However, there is a lack of clarity as to if and why these types of interventions might be effective. Methods: This systematic review examined the intervention characteristics, and behaviour change theory and techniques used in these interventions to promote physical activity for daughters and their mothers. PubMed, EMBASE, PsycINFO, CINAHL and Cochrane Library (Wiley) databases were searched for English language studies from inception to 13th May 2020. Interventions of any design that targeted daughters and mothers' physical activity were included in the review. Data was extracted using the Template for Intervention Description and Replication checklist, and the Behaviour Change Technique Taxonomy v1. Results: 4962 articles were screened and 11 unique studies met the inclusion criteria. Risk of bias was generally high. Narrative summary highlighted that many studies used social cognitive theory as a theoretical foundation, were based in the community and less than three months in duration with multiple sessions per week. Thirty-seven behaviour change techniques were identified across studies. Some techniques were deemed potentially effective including credible source, information on the health consequences of the behaviour and the self-regulatory related techniques of goal-setting, self-monitoring and problem-solving. Conclusions: Future research should consider using checklists, frameworks and formative work with mothers and daughters to ensure interventions are rigorously designed, implemented, and evaluated, which can inform public policy to combat physical inactivity in this at-risk cohort. Key messages: This is the first review to assess the intervention characteristics, and behaviour change theory and techniques of mother-daughter interventions targeting physical activity. This review advances the evidence base for future intervention development and more broadly can inform public policy to tackle physical inactivity in this at-risk cohort.